Exploring Antecedents Affecting Indian Consumers’ Adoption of Mobile Apps: A Study of The Vuca Generation - Vasantha Rao, Taidala; Deepthi, S.; Khairunbi, Sk; Babu Vemula, Prasanth (International Journal of Psychosocial Rehabilitation, 2019)
This research aims to integrate the functional, social, security, and personal dimensions to study mobile app usage antecedents in the Northern Capital Region of India. Convenience sampling was used, and an online survey resulted in 407 valid responses. The measurement and structural models were estimated using PLS-SEM. Perceived usefulness and social influence had no significant impact on usage, implying that contemporary consumers are much more discerning and do not get swayed by the benefits offered or the influence of those around them. The findings show that perceived ease of use had a significant impact on perceived usefulness and attitude formation. Since security is the most important factor determining usage and trust, the industry should have stringent standards to maintain security protocols in every interaction with the user. Also, security concerns need to be allayed, and grievances need to be resolved immediately to gain customer satisfaction and loyalty. Personal innovativeness and lifestyle compatibility are important determinants of attitude and usage. Firms should target mobile apps to students and the active working population who possess innovativeness and for whom mobile apps are compatible with their lifestyle. These users can act as influencers and help in improving their adoption.